VIRTUAL SCREENING OF TRIAZOLES - L., . Mostefaoui, Ghalem S (university of eloued جامعة الوادي, 2020)
Hypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public healthHypertension, or elevated arterial blood pressure, is a substantial public health Hypertension, or elevated arterial blood pressure, is a substantial public health problem. problem. The The The two 11β two 11β two 11β -hydroxysteroid dehydrogenase (11β hydroxysteroid dehydrogenase (11β hydroxysteroid dehydrogenase (11β hydroxysteroid dehydrogenase (11β hydroxysteroid dehydrogenase (11β hydroxysteroid dehydrogenase (11β hydroxysteroid dehydrogenase (11β hydroxysteroid dehydrogenase (11β hydroxysteroid dehydrogenase (11β hydroxysteroid dehydrogenase (11β hydroxysteroid dehydrogenase (11β hydroxysteroid dehydrogenase (11β hydroxysteroid dehydrogenase (11β -HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of HSD) isozymes catalyze the interconversion of cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with cortisol and cortisone. Our research consists in studying the inhibition of enzymes with some derivatives of 1,2,4 some derivatives of 1,2,4 some derivatives of 1,2,4 some derivatives of 1,2,4 some derivatives of 1,2,4 some derivatives of 1,2,4 some derivatives of 1,2,4 some derivatives of 1,2,4some derivatives of 1,2,4 -triazoles triazoles triazoles by means of molecular docking and by means of molecular docking and by means of molecular docking and by means of molecular docking and by means of molecular docking and by means of molecular docking and by means of molecular docking and by means of molecular docking and by means of molecular docking and by means of molecular docking and by means of molecular docking and by means of molecular docking and by means of molecular docking and by means of molecular docking and by means of molecular docking and by means of molecular docking and dynami cs approaches.approaches. approaches.approaches.approaches.approaches. The interac tions betwee n the studied inhibito rs and our target were werewere further explored through molec ular docking and molec ular dynamics simulations, in the presence of , in the presence of , in the presence of , in the presence of , in the presence of , in the presence of , in the presence of , in the presence of , in the presence of , in the presence of , in the presence of , in the presence of water molecules. water molecules. water molecules. water molecules. water molecules. water molecules. water molecules. The The molec ular dynamics study was done for the best der study was done for the best derstudy was done for the best der study was done for the best der study was done for the best der study was done for the best derstudy was done for the best der study was done for the best derstudy was done for the best der study was done for the best der study was done for the best der study was done for the best der study was done for the best derivatives of ivatives of ivatives of 1,2,4 -triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest triazoles inhibitors (deducted from the docking best scores for L2 and L1, lowest score for Lref) score for Lref) score for Lref)score for Lref) score for Lref) score for Lref) score for Lref)score for Lref) . A few key residu es (N-14 with 14 with oxygen receptor interaction H oxygen receptor interaction H oxygen receptor interaction H oxygen receptor interaction Hoxygen receptor interaction Hoxygen receptor interaction H oxygen receptor interaction H oxygen receptor interaction Hoxygen receptor interaction Hoxygen receptor interaction Hoxygen receptor interaction Hoxygen receptor interaction H oxygen receptor interaction H oxygen receptor interaction H- donor) donor) at the binding site of of (11β (11β (11β -HSD1) and (11β HSD1) and (11β HSD1) and (11β HSD1) and (11β HSD1) and (11β HSD1) and (11β -HSD2) were HSD2) were HSD2) were HSD2) wereHSD2) were identified. Obtained Docking and btained Docking and btained Docking and btained Docking and btained Docking and btained Docking and btained Docking and molecular dynami cs result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted result, both leads to the same conclusion and predict that L2 subsisted derivatives of 1, 2, 4 derivatives of 1, 2, 4 derivatives of 1, 2, 4 derivatives of 1, 2, 4 derivatives of 1, 2, 4 -triazoles is the best inhibitor candidate. triazoles is the best inhibitor candidate.triazoles is the best inhibitor candidate.triazoles is the best inhibitor candidate. triazoles is the best inhibitor candidate. triazoles is the best inhibitor candidate. triazoles is the best inhibitor candidate. triazoles is the best inhibitor candidate. triazoles is the best inhibitor candidate. triazoles is the best inhibitor candidate.triazoles is the best inhibitor candidate.
artical
Keywords: 11 β-HSD1 HSD1HSD1; 11 β–HSD2HSD2HSD2HSD2; Hyper HyperHypertensiotensiotensiotensio tension ; 1,2,41,2,4 1,2,4-TriazolesTriazoles TriazolesTriazolesTriazoles Triazoles ; Bioactivity ioactivity ioactivity ioactivity PropertiesProperties Properties Properties ; (Molecular olecular OperaOpera Opera ting Enviro nment)ent)